Comfort, consistency, and efficiency of garments with textile electrodes versus hydrogel electrodes for neuromuscular electrical stimulation in a randomized crossover trial - Ehsan Jafari; Maël Descollonges; Gaëlle Deley; Julie Di Marco; Lana Popovic-Maneski; Amine Metani (Scientific Reports)
Abstract The efficacy and comfort of neuromuscular electrical stimulation (NMES) largely depend on the type of electrodes used. Traditional self-adhesive hydrogel electrodes, while effective, pose limitations in terms of wearability, skin compatibility, and reusability. This randomized crossover trial investigates the performance of a specific textile electrode integrated into garments for NMES of lower extremities, focusing on their potential rehabilitative applications for patients with neurological disorders such as stroke, multiple sclerosis (MS), and spinal cord injury (SCI). In this randomized crossover design, ten healthy subjects participated in the study. Each subject performed isometric knee extension exercises using both textile and hydrogel electrodes in random order. The electrodes were compared in terms of comfort, temporal consistency, stimulation efficiency, and electrical impedance under isometric conditions. Our findings revealed no significant difference between the two types of electrodes across all evaluated parameters. Textile electrodes, used after applying moisturizing lotion to enhance the electrode-skin interface, demonstrated comparable levels of comfort, consistency, and efficiency to hydrogel electrodes. The equivalence of textile and hydrogel electrodes, coupled with the advantages of washability and reusability, positions textile electrodes as a promising alternative for NMES applications, particularly in rehabilitation settings.